The interaction between gender and the number of brothers on creativity in Sudanese pupils: A cross-sectional study using the Torrance Test of Creative Thinking-Figural (TTCT-Figural) performance - Abdo Hasan AL-Qadri; Mohammed Ateik Al-Khadher; Salaheldin Farah Bakhiet; Ismael Salamah Albursan; Benbrahim Halima; Qais I.S. Al-Meqdad (Acta Psychologica)
The Torrance Test of Creative Thinking (TTCT) is commonly used to assess creativity in pupils, but research is limited on its effectiveness in identifying cognitive levels and how factors like gender and brothers count influence creativity. This study investigates the interaction between gender and the number of brothers on creativity as assessed by the (TTCT-Figural: Circles test) among students aged 7 to 13. A cross-sectional study design was employed, involving a sample of 11,636 students, including 5571 males (47.9 %) and 6065 females (52.1 %), selected from public and private schools across Sudan. The findings demonstrated an interaction effect between gender and the number of brothers, revealing significant gender differences in (TTCT-Figural) performance, particularly across the domains of fluency, flexibility, and originality, with females outperforming males in all three areas. Notably, no gender differences in flexibility were observed at ages 10 and 13, nor in fluency at age 13, and originality showed no gender disparity across all age groups. Additionally, TTCT-Figural performance did not vary significantly across different age groups. The majority of students exhibited very low performance at age 7, with slight improvements noted at ages 8 and 9. However, after age 9, there was a decline in the number of students performing at a moderate level. Moreover, these results emphasize the importance of understanding the role of gender and familial factors, such as the number of brothers, in creativity development. The implications of this study suggest the need for targeted educational programs and policies intended at enhancing (TTCT-Figural) performance, particularly for pupils, to adoptive creativity further effectively.